Alleviate Periodontitis and Its Comorbidity Hypertension using a Nanoparticle‐Embedded Functional Hydrogel System - Xu, Shuo; Hu, Bin; Dong, Ting; Chen, Bo‐Yan; Xiong, Xiao‐Jian; Du, Lin‐Juan; Li, Yu‐Lin; Chen, Yan‐Lin; Tian, Guo‐Cai; Bai, Xue‐Bing; Liu, Ting; Zhou, Lu‐Jun; et al. (Advanced healthcare materials, 2023)
Periodontitis and hypertension often occur as comorbidities, which need to be treated at the same time. To resolve this issue, a controlled‐release composite hydrogel approach is proposed with dual antibacterial and anti‐inflammatory activities as a resolution to achieve the goal of co‐treatment of comorbidities. Specifically, chitosan (CS) with inherent antibacterial properties is cross‐linked with antimicrobial peptide (AMP)‐modified polyethylene glycol (PEG) to form a dual antibacterial hydrogel (CS‐PA). Subsequently, curcumin loaded into biodegradable nanoparticles (CNP) are embedded in the hydrogel exhibiting high encapsulation efficiency and sustained release to achieve long‐term anti‐inflammatory activities. In a mouse model of periodontitis complicated with hypertension, CS‐PA/CNP is applied to gingival sulcus and produced an optimal therapeutic effect on periodontitis and hypertension simultaneously. The therapeutic mechanisms are deeply studied and indicated that CS‐PA/CNP exerted excellent immunoregulatory effects by suppressing the accumulation of lymphocytes and myeloid cells and enhanced the antioxidant capacity and thus the anti‐inflammatory capacity of macrophages through the glutathione metabolism pathway. In conclusion, CS‐PA/CNP has demonstrated its superior therapeutic effects and potential clinical translational value in the co‐treatment of periodontitis and hypertension, and also serves as a drug delivery platform to provide combinatorial therapeutic options for periodontitis with complicated pathogenesis. CS‐PA hydrogel with dual antibacterial activities is fabricated through the thiol‐maleimide click reaction, where curcumin nanoparticles are physically incorporated. By in situ injection of the hydrogel into periodontal pockets, CS‐PA/CNP can inhibit various periodontal pathogens and restore immune hemostasis to effectively manage periodontitis, which reverses periodontitis‐exacerbated hypertension in the meantime.